Determination of cyclamate in urine by derivatized gas chromatography-mass spectrometry - Mohd Idris; Deepak Middha; Shaik N Rasool; Sudhir K Shukla; Tulsidas R Baggi (Wolters Kluwer Medknow Publications, 2013)
Aim: It is important in toxicological/drug screening work to rule out the possible interfering analytes, to eliminate the false positive or negative results. In this paper, we describe a simple, selective, and sensitive derivatized GC-MS method for the determination of cyclohexylsulfamic acid (cyclamate) in urine. Materials and Methods: Elite- 5MS capillary column was used for the separation of analytes and detection using GC-MS. The analysis was carried out in selected ion monitoring mode (SIM) in the range of 26 to 200 using m/z values of 57, 30, 55, 41, 44, 67, 82, 98, and 39. Results and Discussion: The method is based on the conversion of cyclamate into nitroso derivative of cyclamate followed by its gas chromatography-mass spectrometry determination. The limit of detection, limit of quantitation, and linearity range of the proposed method were found to be 0.2 μg/ ml, 0.7 μg/ml, and 1-15 μg/ml, respectively. The recovery of the present method is in the range of 88-94%. Conclusion: The proposed method can be applied for detection and quantification of cyclamate in urine.